2021
DOI: 10.1002/saj2.20237
|View full text |Cite
|
Sign up to set email alerts
|

Total extractable phosphorus in flooded soil as affected by struvite and other fertilizer‐phosphorus sources

Abstract: A sustainable P source is imperative to ensure that food production can supply a growing global population. Wastewater-recovered struvite (MgNH 4 PO 4 • 6H 2 O) has emerged as an attractive option because of the ability to recover P from waste streams.This study aimed to evaluate total extractable soil P from electrochemically precipitated struvite (ECST) compared with other fertilizer-P sources [chemically precipitated struvite (CPST), diammonium phosphate (DAP), and rock phosphate] in two soil textures (two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…The consistent similarities in plant response from the two struvite materials (ECST and CPST) suggest that the difference in physical form applied (i.e., crystalline for ECST and prill for CPST) between the struvite sources had little to no effect on P release and behavior of the materials. Anderson et al (2021b) reported a similar incremental increase from the initial value of water-soluble and Mehlich-3 soil P concentrations between ECST-and CPSTtreated soil in a silty clay loam and two silt-loam soils under flooded condition after 1, 2, 3, and 4 mo of a plant-less soil incubation study.…”
Section: Source Of Variationsupporting
confidence: 53%
See 2 more Smart Citations
“…The consistent similarities in plant response from the two struvite materials (ECST and CPST) suggest that the difference in physical form applied (i.e., crystalline for ECST and prill for CPST) between the struvite sources had little to no effect on P release and behavior of the materials. Anderson et al (2021b) reported a similar incremental increase from the initial value of water-soluble and Mehlich-3 soil P concentrations between ECST-and CPSTtreated soil in a silty clay loam and two silt-loam soils under flooded condition after 1, 2, 3, and 4 mo of a plant-less soil incubation study.…”
Section: Source Of Variationsupporting
confidence: 53%
“…Thus, fertilizer-P sources commonly used in agriculture tend to be substantially more soluble than struvite. Consequently, the solubility characteristics make struvite a potentially ideal, slow-release P source for many types of plants, including agricultural crops, in upland, well-drained (Achat et al, 2014;Anderson et al, 2021a;Thompson, 2013) and lowland, poorly drained soils (Anderson, Anderson, Brye, Greenlee, & Roberts, 2021;Anderson et al, 2021b).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Anderson et al (2020), Anderson, Brye, Kekedy-Nagy, et al (2021), for each fertilizer material, five subsamples were used for chemical analyses. Soil pH was measured potentiometrically in a 1:2 fertilizer mass/water volume ratio (Sikora & Kissel, 2014).…”
Section: Fertilizer-p Sources and Analysesmentioning
confidence: 99%
“…After procedures and the same soils used in Anderson et al (2020), Anderson, Brye, Kekedy-Nagy, et al (2021) and procedures used for fertilizer material analyses, triplicate soil subsamples were characterized for physical (i.e., particle-size distribution) and chemical analyses (i.e., pH, EC, soil organic matter [SOM], total C, total N, and WS and M3 elemental concentrations [P, Ca, Mg, and Fe]). Soil subsamples were also extracted with 2 M KCl in a 1:5 soil mass/extractant volume ratio and analyzed spectrophotometrically to determine initial NO 3 -N and NH 4 -N concentrations by the cadmium-reduction and salicylate methods, respectively (Mulvaney, 1996).…”
Section: Soil Collection and Analysesmentioning
confidence: 99%